Model‐based meta‐analysis of the time to first acute urinary retention or benign prostatic hyperplasia‐related surgery in patients with moderate or severe symptoms. Issue 7 (19th January 2021) - D'Agate, Salvatore; Chavan, Chandrashekhar; Manyak, Michael; Palacios‐Moreno, Juan Manuel; Oelke, Matthias; Michel, Martin C.; Roehrborn, Claus G.; Della Pasqua, Oscar
Abstract : Aims: Combination therapy of 5α‐reductase inhibitor and α‐blocker is a guideline‐endorsed therapeutic approach for patients with moderate‐to‐severe lower urinary tract symptoms or benign prostatic hyperplasia (LUTS/BPH) who are at risk of disease progression. We aimed to disentangle the contribution of clinical and demographic baseline characteristics affecting the risk of acute urinary retention or BPH‐related surgery (AUR/S) from the effect of treatment with drugs showing symptomatic and disease‐modifying properties. Methods: A time‐to‐event model was developed using pooled data from patients (n = 10 238) enrolled into six clinical studies receiving placebo, tamsulosin, dutasteride or tamsulosin‐dutasteride combination therapy. A parametric hazard function was used to describe the time to first AUR/S. Covariate model building included the assessment of relevant clinical and demographic factors on baseline hazard. Predictive performance was evaluated by graphical and statistical methods. Results: An exponential hazard model best described the time to first AUR/S in this group of patients. Baseline International Prostate Symptom Score, prostate‐specific antigen, prostate volume and maximum urine flow were identified as covariates with hazard ratio estimates of 1.04, 1.08, 1.01 and 0.91, respectively. Dutasteride monotherapy and tamsulosin‐dutasteride combination therapy resulted in a significant reduction in the baseline hazard (56.8% and 66.4%, respectively). By contrast, the effect of tamsulosin did not differ from placebo. Conclusions: Our analysis showed the implications of disease‐modifying properties of dutasteride and tamsulosin‐dutasteride combination therapy for the risk of AUR/S. It also elucidated the contribution of different baseline characteristics to the risk of these events. The use of tamsulosin monotherapy (symptomatic treatment) has no impact on individual long‐term risk. Abstract : Visual predictive checks. The line shows observed survival over time, whereas the shaded area describes the model predicted 95% CI for the survival. The different slopes of the survival curves for dutasteride monotherapy and combination therapy (relative to placebo) reflect the disease‐modifying properties of the intervention.